2021
DOI: 10.3390/ijerph18147706
|View full text |Cite
|
Sign up to set email alerts
|

Functioning and Happiness in People with Schizophrenia: Analyzing the Role of Cognitive Impairment

Abstract: Schizophrenia is associated with marked functional impairment and low levels of subjective happiness. The aim of the current study was to evaluate the relationship between subjective happiness and functioning in patients with schizophrenia, while considering the role of cognitive functioning. Methods: In total, 69 schizophrenia patients and 87 matched healthy controls participated in the study. Patients’ clinical status was assessed, and a series of self-report questionnaires were administered to both patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…This neglect may reflect stigma toward those with SMI. The findings from this study, while preliminary, suggest that happiness and well-being should be an important consideration during service planning (Fervaha et al, 2016;Gutiérrez-Rojas et al, 2021;Mankiewicz et al, 2013;Palmer et al, 2014;Rekhi et al, 2021). Given the significance contribution of being a parent or grandparent to several participants' happiness, more attention should also be directed toward promoting successful parenting outcomes for persons enrolled in psychiatric rehabilitation programs (Dubreucq et al, 2021).…”
Section: Implications For Cliniciansmentioning
confidence: 73%
See 2 more Smart Citations
“…This neglect may reflect stigma toward those with SMI. The findings from this study, while preliminary, suggest that happiness and well-being should be an important consideration during service planning (Fervaha et al, 2016;Gutiérrez-Rojas et al, 2021;Mankiewicz et al, 2013;Palmer et al, 2014;Rekhi et al, 2021). Given the significance contribution of being a parent or grandparent to several participants' happiness, more attention should also be directed toward promoting successful parenting outcomes for persons enrolled in psychiatric rehabilitation programs (Dubreucq et al, 2021).…”
Section: Implications For Cliniciansmentioning
confidence: 73%
“…Unfortunately, few studies have explored either happiness or SWB for people with serious mental illness (SMI; Agid et al, 2012; Gutiérrez-Rojas et al, 2021; Slade, 2010), although both are important aspects of positive human experience both for their immediate emotional qualities and because they predict other positive outcomes, including mental health, life satisfaction, social relationships, physical health, and even longevity (Diener & Seligman, 2004; Lyubomirsky et al, 2005). Of the small group of empirical studies conducted in this area, most have either compared the happiness and well-being of people with SMI, especially schizophrenia, with a healthy comparison group (Agid et al, 2012; Fervaha et al, 2016; Gutiérrez-Rojas et al, 2021; Palmer et al, 2014) or have examined within group correlates (Rekhi et al, 2021). The preponderance of results report that people with SMI are on average less happy than the general population (see Agid et al, 2012 for an exception, in a small study of young adults with first episode psychosis), though there is considerable variance among people with SMI and many of these individuals may generally be happy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenia negatively affects happiness [ 16 ], but happiness can still be an achievable goal for people with this disorder [ 17 ]. This finding confirms Saks’s [ 18 ] claim that people with schizophrenia can find “well-being within the disease”.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies specifically focused on understanding happiness in severe mental disorders [ 8 , 12 , 13 , 16 , 17 , 19 ]. Some studies have found lower levels of happiness in patients diagnosed with schizophrenia [ 7 , 8 , 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%